Identification of Active Compounds of Leaf Extract and Seed Oil of Moringa oleifera in TrkB Receptor as Neuroprotective by Molecular Docking - Muhamad Sadam Safutra; Fadilah; Wawaimuli Arozal; Agian Jeffilano Barinda (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
The functional ability of the brain will decline progressively during aging which usually involves changes in plasticity. BDNF is one of the neurotrophins that regulates plasticity via TrkB receptors. So the potential of Moringa oleifera leaf and seed oil extracts was identified as neuroprotective on the interaction of TrkB receptors with molecular docking. The active compounds of Moringa oleifera leaf extract and seed oil were obtained from literature studies. Drug-likeness and ADMETox analysis were carried out using the SwissAdme and the AdmetSAR webserver. The molecular docking was carried out using the Pyrx Vina application and visualization is done using the Discovery Studio Biovia application. The docking results showed the best compounds namely luteolin, stigmasterol, and moringin as a marker compound and showed the interaction of hydrogen and hydrophobic bonds at the active site of the prediction results. So it can be concluded that compounds in the leaves and seed oil of Moringa oleifera, namely luteolin, stigmasterol, and moringin are predicted as ingredients that can activate TrkB receptors in the aging process.